2005
DOI: 10.1200/jco.2005.16.584
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Safety, Pharmacokinetics, and Clinical Activity Study of Lapatinib (GW572016), a Reversible Dual Inhibitor of Epidermal Growth Factor Receptor Tyrosine Kinases, in Heavily Pretreated Patients With Metastatic Carcinomas

Abstract: Lapatinib was well tolerated at doses ranging from 500 to 1,600 mg once daily. Clinical activity was observed in heavily pretreated patients with ErbB1-expressing and/or ErbB2-overexpressing metastatic cancers, including four PRs in patients with trastuzumab-resistant breast cancers and prolonged stable disease in 10 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
392
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 584 publications
(418 citation statements)
references
References 31 publications
23
392
0
3
Order By: Relevance
“…We then studied the effect of another ErbB2-targeting agent, GW583340, which has similar composition as the clinical compound lapatinib/Tykerb and has been shown to be more effective compared with trastuzumab in inhibiting ErbB2 signaling and inducing tumor apoptosis in ErbB2-overexpressing advanced metastatic breast cancer patients (17) and breast tumor lines (18,29,35,36). Immunoblot analysis of the cell lysates at 48 h post-GW583340 treatment revealed a significant inhibition of p-AKT expression at the lowest concentration of 1 Amol/L with complete inhibition at higher concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then studied the effect of another ErbB2-targeting agent, GW583340, which has similar composition as the clinical compound lapatinib/Tykerb and has been shown to be more effective compared with trastuzumab in inhibiting ErbB2 signaling and inducing tumor apoptosis in ErbB2-overexpressing advanced metastatic breast cancer patients (17) and breast tumor lines (18,29,35,36). Immunoblot analysis of the cell lysates at 48 h post-GW583340 treatment revealed a significant inhibition of p-AKT expression at the lowest concentration of 1 Amol/L with complete inhibition at higher concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, subsets of women with ErbB2-overexpressing tumors do not respond and resistance is common (15,16). Lapatinib (GW583340/ GW572016/Tykerb), a dual inhibitor of the oncogenic ErbB2 and ErbB1 receptor tyrosine kinases, blocks ErbB2 tyrosine autophosphorylation with consequential downstream inhibitory effects on MAPK-Erk1/2 and PI3K-Akt growth/survival signaling in tumor cell lines, tumor xenografts, and in patients, notably those with ErbB2-overexpressing breast cancers where lapatinib induces tumor cell apoptosis (17)(18)(19). In a recent clinical trial, lapatinib showed a 50% clinical response rate in ErbB2-overexpressing IBC patients compared with ErbB2 overexpressing non-IBC patients (20); however, acquired resistance is a common outcome even in those patients who show an initial clinical response.…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/reviews/cancer in LVEF were observed 32 , despite pharmacodynamic evidence of inhibition of ERBB2 signalling in breast cancer cell lines and patient tumour samples. Although a definitive safety profile for lapatinib must await the completion of several randomized phase III trials in breast cancer, it seems likely that the frequency of cardiac dysfunction will be low.…”
Section: Box 1 | Haematological Cancers: Good Targets For Tyrosine Kimentioning
confidence: 96%
“…If inhibition of ERBB2 signalling induces cardiomyocyte dysfunction, then cardiotoxicity would also be expected with small-molecule inhibitors of ERBB2 kinase activity. However, early clinical results with lapatinib (GW572016), a quinazoline compound that is an orally available dual kinase inhibitor of EGFR and ERBB2, suggest that it has minimal cardiotoxicity 32 . Because of the trastuzumab experience, prospective monitoring of cardiac function is an integral part of phase I-III trials of lapatinib.…”
Section: Molecular Mechanisms Of Trastuzumab Cardiotoxicitymentioning
confidence: 99%
“…No thorough exposure–response or exposure–toxicity studies have been reported for lapatinib, although one trial found that the majority of responders had a C min in the 300–600 ng/ml range 37. Future studies should focus on establishing exposure–response and exposure–toxicity relationships.…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 99%